Action Plans to Reduce PM2.5 Concentrations in Hotspots of Delhi-NCR Using a One-way Coupled Modeling Approach - Shubham Sharma; Mukesh Khare; Sri Harsha Kota (Aerosol and Air Quality Research)
Abstract The concentration of PM2.5 in Delhi, one of the most polluted capital cities globally, frequently exceeds the Indian National Ambient Air Quality Standards, especially during the post-monsoon and winter months. This study evaluates the changes in PM2.5 concentrations across Delhi using a one way coupled model (WRF-CMAQ-AERMOD) for various hotspot-specific intervention scenarios during post-monsoon and winter of 2018. PM2.5 concentrations reduced up to 15% by scaling down total emissions across Delhi by 20%. An additional 9% reduction across entire Delhi and ~28% reduction at the top ten observation-based hotspots could be achieved if emissions of industry, unpaved road dust and construction in selected emission hotspots are made zero. Non-local contribution in hotspots of the city varied significantly. For example, the difference in the reductions of PM2.5 concentrations from citywide versus hotspot-specific interventions is estimated to be 28% at DU North Campus and 11% at Anand Vihar. An average reduction of 12% was computed when construction and MSW burning emissions were down sized 100% in the locations identified based on compliance complaints received at the Central Pollution Control Board’s online complaint portal. A marginal reduction of 4% estimated for the previously implemented traffic rationing measure, the odd-even rule, indicates that such regulation of vehicles alone might be inefficacious. The results suggest that stakeholders must focus on—(a) source and hotspot-specific interventions alongside city wide interventions to significantly reduce ambient PM2.5 concentrations, (b) local and non-local contributions from regions outside the hotspot grid needs to be carefully considered for estimating efficacy of an action plan.